Mixed Methods Inquiry To Explore Nurses’ Views and Opinions about Dementia Care Nursing In Non-Dementia Specific Wards/Units Contained In Dedicated Health Care Services For Older Persons Linked to Acute Hospital Services - Ayton, Anna Christina (University of Dublin, Trinity College Dublin. School of Nursing and Midwifery, 2019)
Background - The older population (>65 years) is increasing in number. There is a concomitant rise in the numbers of older persons living with dementia, as there is a distinct correlation between ageing and dementia. Dementia is frequently accompanied by three or more multi-morbidities. Older persons with dementia accompanied by multi-morbidities are amongst the highest consumers of health care services. Due to these facts, nurses are encountering an increasing number of older persons with a co-incidental dementia in their daily practice. This includes nurses practicing in non-dementia specific wards/units that include acute, rehabilitation and residential, contained in dedicated health care services for the older person linked to acute hospitals. This is the area of interest in the current study. Due to the demographic changes in our population and, the increasing prevalence of dementia along with the dearth of nursing research conducted in this unique research setting, provided justification for the current study. Research Aim - The aim of this two phase mixed methods sequential explanatory study was to explore nurses’ views and opinions about dementia care nursing based on their experiences of caring for the older person with dementia in non-dementia specific wards/units that include acute, rehabilitation and residential, contained in dedicated health care services for the older person linked to acute hospital services in the Irish context. Methodology - A mixed methods sequential explanatory design was used. Phase one involved a quantitative survey approach with nurses (n=129) from non-dementia specific wards/units that include acute, rehabilitation and residential, contained in dedicated health care services for the older person linked to three acute general hospitals. Three questionnaires along with a demographic questionnaire were used to gather data relative to the nurses’ views and opinions about various aspects of dementia care nursing to include nurses’ attitudes towards dementia and nurses’ beliefs about the environment of care. Phase two involved, running five focus groups within the same non-dementia specific setting. Altogether 25 registered general nurses participated in the focus group interviews. The purpose of the focus groups interviews was to elaborate on the quantitative responses from phase one. Findings - Nurses were found to be generally positive about dementia care nursing and positive attitudes correlated significantly with specialist qualifications, management grades and > 11 years of nursing experience, 37.2% of the respondents had specialist qualifications. Key findings highlighted the need for organisational support to place an emphasis on access to specialist training and education to ensure that all nurses are adequately equipped to provide dementia care nursing. A significant finding was that in light of the many ethical dilemmas encountered in dementia care nursing, nurses would welcome the opportunity to participate in clinical supervision and education specific to ethics to enhance their competencies in ethical decision making. The participants represented a culturally diverse group of nurses. A unique finding related to cultural understandings of dementia and dementia care nursing and the impact on dementia care nursing and the importance of recognising and addressing this at the point of integration into the nursing role. While many nurses expressed satisfaction with the physical environment of care, others voiced concern, particularly in relation to the challenges of maintaining persons with dementia safety and security within the ward environment. In relation to staffing levels, many nurses perceived that insufficient staffing levels resulted in challenges in providing the quality of dementia care nursing that they wanted to deliver and that they knew the person with dementia deserved. Conclusion - Results of the study, contribute an overview of the experiences of nurses within the unique setting of non-dementia specific wards/units as identified. An array of complexities experienced by nurses in their practice of dementia care nursing, were identified. Specialist dementia education is critical to ensure that all nurses are providing dementia care nursing according to the person-centred philosophies of the organisation.
Keywords: Dementia care nursing